Review of the literature - Methods of external and internal training load monitoring in elite tennis environments. - Murphy, A. P. (Journal of Australian Strength and Conditioning, 2013)
This review addresses the methods of both external and internal workload monitoring in elite level tennis environments with discussion of long term athlete development. Limited studies have provided specific examples of workload monitoring strategies for contemporary tennis populations, whilst many studies in other sporting populations have developed monitoring initiatives which tennis has the potential to adopt. Monitoring of both training and competition loads have been identified as vital performance tracking indicators in modern day, elite tennis environments. Therefore, appropriate workload monitoring techniques play an important role in elite level athlete development. Tennis is a sport involving both a fine skill component as well as vast physical requirements. Consequently, elite level sporting organisations such as tennis demand strict, but individualised, program periodisation to ensure that tactical and technical components along with athlete physicality, are developed in unison. However, research evidence on the implementation of workload monitoring in tennis is limited and it is unclear to what extent workload monitoring application can influence athlete skill and physical progression. As such, this review highlights the appropriateness of heart rate (HR) and rate of perceived exertion (RPE) measures for monitoring internal training load (TL), as well as the future potential of external load monitoring through global positioning system (GPS) and motion tracking analysis.